'I want to be judged on my work, I don't want to be judged as a person': Inequality, expertise and cultural value in UK craft. (December 2022) - Patel, Karen
This article focuses on the relationship between inequality, expertise and cultural value in UK professional craft. Drawing on interviews with ethnically diverse women makers, I explore how getting their craft skills recognised and valued as expertise hinders their ability to establish a full-time career in craft. This is because judgements of craft expertise are largely predicated on aesthetic codes and classifications which are historically racialised, gendered and classed. In order to address these exclusionary processes, I argue that expertise in craft, which refers to the practical skills of production and the capacities of the maker, should be more central to evaluative judgements. I draw on Janet Wolff's work on community evaluation to discuss how evaluative judgements about craft expertise can be less universalizing and instead located within specific contexts and communities. I propose that community evaluation could help to reframe what ideas of craft expertise are and address existing inequalities in the sector.